Detection of Treponema pallidum in lesion exudate with a pathogen-specific monoclonal antibody. - Hook, E W (1985)
The diagnosis of early syphilis currently requires dark-field microscopic or serologic demonstration of Treponema pallidum infection. Dark-field microscopy is not widely available and is complicated by the numerous saprophytic spirochetes which are present at oral and rectal mucosal surfaces. Serologic tests are positive in only 70 to 90% of patients with primary syphilis, and several days may be required for results to become available. We used a pathogen-specific, fluorescein-conjugated monoclonal antibody to examine lesion exudates from 61 patients for the presence of T. pallidum and compared the data with results of dark-field microscopy and serologic testing. The direct fluorescent-antibody technique revealed the presence of T. pallidum in 30 of 30 patients with early syphilis, and dark-field microscopy was positive for 29. Serologic tests were reactive for 27 of 30 patients with syphilis; in the 3 patients with nonreactive serologic tests, chancres had been present for 4, 6, and 21 days. Although 7 of 31 patients without syphilis had spiral organisms seen on dark-field microscopy, the direct fluorescent-antibody test was negative for all 31. The presence of nonpathogenic spirochetes was subsequently verified in 5 of 7 patients by using a second monoclonal antibody which reacts with nonpathogenic, as well as pathogenic, treponemes and related spirochetes. The demonstration of T. pallidum by using fluorescein-conjugated monoclonal antibodies is intrinsically specific and is as sensitive as dark-field microscopy for the diagnosis of early syphilis. This method provides a convenient, accurate means for the diagnosis of syphilis by health care providers, many of whom lack access to dark-field microscopy.